Analisis Manajemen Kelompok Tani dalam Mempertahankan Keberlanjutan Program - Herwanto, Puja Maulida; Agista, Putera; Muslim, Muhamad Naufal; Ningtyas, Syaharani Ayu; Mulyana, Hijra Drajat; Siregar, Mariana Rista Ananda (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2025)
The Jamelang Adult Farmers Group or as known as Kelompok Tani Dewasa (KTD) located in Kedunghalang Village, Bogor City, was established by the community to implement a program aimed at empowering society and enhancing food security through hydroponic farming. This study aims to understand how KTD Jamelang manages to sustain the Hidroponik Barokah program after the termination of the Corporate Social Responsibility (CSR) support from the Yayasan Baitul Mal (YBM) BRI. The research employs a qualitative approach, utilizing field observations and in-depth interviews to gain a comprehensive understanding. The findings indicate that the sustainability of this program is supported by participatory communication management, which involves members in decision-making and ensures transparency in financial and operational matters. Continuous guidance from the KTD Jamelang facilitator is also a key factor in the sustainability of the Hydroponic Barokah program. Additionally, the Hydroponic Barokah program has positively impacted KTD Jamelang members, leading to increased productivity, knowledge, and income. Furthermore, social support, networking, and market access significantly contribute to the program's sustainability.